Special issue on modeling people: Vision-based understanding of a person`s shape, appearance, movement and behaviour (Computer Vision and Image Understanding, 2006)
Modeling people: Vision-based understanding of a person`s shape, appearance, movement, and behaviour (A. Hilton, P., R. Ronfard) A survey of advances in vision-based human motion capture and analysis (Thomas B. Moeslund, Adrian Hilton, Volker Krüger) Human body pose detection using Bayesian spatio-temporal templates (M. Dimitrijevic, V. Lepetit, P. F.) Learning-based dynamic coupling of discrete and continuous trackers (Gabriel Tsechpenakis, Dimitris Metaxas, Carol Neidle Temporal motion models for monocular and multiview 3D human body tracking (Raquel Urtasun, David J. Fleet, Pascal F.) Viewpoint invariant exemplar-based 3D human tracking (Eng-Jon Ong, Antonio S. Micilotta, Richard Bowden, Adrian Hilton) Markerless tracking of complex human motions from multiple views (Roland Kehl, Luc Van Gool) Conditional models for contextual human motion recognition (Cristian Sminchisescu, Atul Kanaujia, Dimitris Metaxas) Matching actions in presence of camera motion (Alper Yilmaz, Mubarak Shah) A general method for human activity recognition in video (Neil Robertson, Ian Reid) Free viewpoint action recognition using motion history (Daniel Weinland, Remi Ronfard, Edmond Boyer)